Assessing the impact of vaccination and medical resource allocation on infectious disease outbreak management: a case study of COVID-19 in Taiyuan City - Guo, Jiaming; Luo, Yuxin; Ma, Yifei; Xu, Shujun; Li, Jiantao; Wang, Tong; Lei, Lijian; He, Lu; Yu, Hongmei; Xie, Jun (Frontiers in Public Health, 2024)
Amidst an emerging infectious disease outbreak, the rational allocation of vaccines and medical resources is crucial for controlling the epidemic’s progression. Analysing COVID-19 data in Taiyuan City from December 2022 to January 2023, this study constructed a dynamics model to assess the impact of COVID-19 vaccination and resource allocation on epidemic trends. Results indicate that vaccination significantly reduces infection rates, hospitalisations, and severe cases, while also curtailing strain on medical resources by reducing congestion periods. An early and sufficient reserve of medical resources can delay the onset of medical congestion, and with increased maximum capacity of medical resources, the congestion’s end can be accelerated. Stronger resource allocation capabilities lead to earlier congestion resolution within a fixed total resource pool. Therefore, integrating vaccination and medical resource allocation can effectively reduce medical congestion duration and alleviate the epidemic’s strain on medical resource capacity (CCMR).